Urgency of Multicultural Islamic Education on Modern Indonesian Education - S., Sumarni; Aisyah, Neng; Abdurrahmansyah; Handayani, Tutut (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Examining the necessity of multicultural Islamic education in contemporary Indonesian school is the goal of this study. This study employed library research as its methodology. Both primary and secondary data sources are used in the data collection for this study. The author applies analytical descriptive data analysis approaches to the data analysis. Specifically, information about the subject of the study is gathered, categorized, explained, and ultimately concluded. According to the study's findings, multicultural education is thought to be the greatest way to address the diversity that already exists in society, including differences in culture, religion, ethnicity, and other areas, by encouraging an appreciation of diversity. Since Allah SWT created humanity and nature with great diversity, differences are a blessing rather than something to be despised or viewed as sinful. Therefore, multicultural education must be seen as a practical aspect of multiculturalism, where one must put the theory into practice by taking actual action in addition to understanding it.